MSE wall geogrid tensile strength at high temperature sites. Issue 1 (11th April 2014) - Kasozi, Andrew M.; Siddharthan, Raj V.; Mahamud, Rajib
Abstract : The Nevada Department of Transportation is currently considering to use geosynthetic reinforcements for mechanically stabilised earth walls in Nevada. Geosynthetic reinforcement avoids corrosion and is often cheaper and easier to install during construction. However, specific to conditions in southern Nevada, geosynthetic materials may have other potential degradation issues, for example, uncertainty of long-term field performance at high temperatures. These temperatures may substantially degrade the tensile strength and creep of geosynthetic materials because their mechanical behaviour is temperature sensitive. This study focused on the tensile strength degradation of geogrid reinforcement, in which a simple scheme is proposed to obtain a more realistic strength reduction factor for design, that is, RF D, at high-temperature sites. The scheme combines the effects of the following important design factors: site-specific air temperature history, numerical thermal modelling to establish soil backfill temperatures and laboratory testing at high temperatures. It addresses the effects of both long-term exposure to high temperatures and load level on the design strength of geogrids. The proposed approach has been illustrated using temperature data for Las Vegas, NV, and is easily adaptable to any location and geosynthetic reinforcement.